Just-in-Time Elements and Benefits - García Alcaraz, Jorge Luis; Macías, Aide Aracely Maldonado (Management and Industrial Engineering,, 2016)
This book reports the elements required for implementing Just in Time (JIT) technique in companies. The main reasons for low implementation processes and the main benefits from the successful implementation of them are highlighted in this book. Structural equation models are presented to help identify the essential elements in JIT.